2019
DOI: 10.3847/1538-3881/aaf563
|View full text |Cite
|
Sign up to set email alerts
|

Active Asteroid P/2017 S5 (ATLAS)

Abstract: Observations of active asteroid P/2017 S5 when near perihelion reveal the ejection of large (10 2 to 10 4 µm) particles at 0.2 to 2 m s −1 speeds, with estimated mass-loss rates of a few kg s −1 . The protracted nature of the mass loss (continuous over ∼150 days) is compatible with a sublimation origin, meaning that this object is likely an ice-bearing main-belt comet. Equilibrium sublimation of exposed water ice covering as little as 0.1 km 2 can match the data. Observations a year after perihelion show the o… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 23 publications
1
12
0
Order By: Relevance
“…This corresponds to the dust velocity V = 40 β/1.78 = 30 √ β m s −1 , broadly consistent with V ⊥ ∼ 20 √ β m s −1 inferred from the perpendicular profile (Section 3.3). Similar model parameters were found for MBCs 238P, 324P, 358P, and P/2017 S5 (Hsieh et al 2009;Moreno et al 2011Moreno et al , 2013Jewitt et al 2019), indicating that these objects share similar properties of the ejected dust.…”
Section: Particle Propertiessupporting
confidence: 68%
“…This corresponds to the dust velocity V = 40 β/1.78 = 30 √ β m s −1 , broadly consistent with V ⊥ ∼ 20 √ β m s −1 inferred from the perpendicular profile (Section 3.3). Similar model parameters were found for MBCs 238P, 324P, 358P, and P/2017 S5 (Hsieh et al 2009;Moreno et al 2011Moreno et al , 2013Jewitt et al 2019), indicating that these objects share similar properties of the ejected dust.…”
Section: Particle Propertiessupporting
confidence: 68%
“…The 427P (P/2017 S5) is interesting from another point of view. Its time-series photometry lightcurve indicates possibly rapid rotation with a period of 1.4 h. Though this period is yet to be confirmed, Jewitt et al (2019) suggested that, if real, it may also play a role in the mass loss. The authors further suggested that such a rapid rotation could be a consequence of spin-up by sublimation torques.…”
Section: Main Properties Of Three Families Associated With the Most Mbcsmentioning
confidence: 98%
“…Comet 427P/ATLAS (hereafter 427P), previously designated P/2017 S5, was discovered on 2017 September 27 by the Asteroid Terrestrial-impact Last Alert System (ATLAS) survey telescope (Heinze et al 2017) when the object was at ν = 21.3°, r h = 2.214 au, and Δ = 1.267 au. Jewitt et al (2019) conducted an observational analysis shortly after its discovery, finding that the comet's activity was due to a prolonged dust-emission event occurring over ∼150 days, consistent with sublimation-driven emission. Using follow-up observations obtained using HST the following year when the object was apparently inactive, Jewitt et al (2019) also estimated 427P's nucleus to have an effective radius of 450 60 100 -+ m, assuming an albedo of p = 0.06 ± 0.02.…”
Section: P/atlasmentioning
confidence: 99%